Diverse BCR usage and T cell activation induced by different COVID-19 sequential vaccinations - Junxiang Wang; Kaiyi Li; Yuan Wang; Zhengfang Lin; Weidong Li; Jinpeng Cao; Xinyue Mei; Rui Wei; Jinglu Yang; Xiaobing Zhai; Deyi Huang; Kaiwen Zhou; et al. (mBio)
ABSTRACT Limited knowledge is available on the differences in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) specific antibody breadth and T cell differentiation among different COVID-19 sequential vaccination strategies. In this study, we compared the immunogenicity of the third different dose of COVID-19 vaccines, such as mRNA (I-I-M), adenoviral vector (I-I-A), and recombinant protein (I-I-R) vaccines, in terms of the magnitude and breadth of antibody response and differentiation of SARS-CoV-2-specific T and B cells. These studies were performed in the same clinical trial, and the samples were assessed in the same laboratory. IGHV1-69, IGHV3-9, and IGHV4-34 were the dominant B cell receptor (BCR) usages of the I-I-M, I-I-A, and I-I-R groups, respectively; the RBD+ B cell activation capacities were comparable. Additionally, the I-I-R group was characterized by higher numbers of regulatory T cells, circulating T follicular helper cells (cTFH) – cTFH1 (CXRC3+CCR6-), cTFH1-17 (CXRC3+CCR6+), cTFH17 (CXRC3-CCR6+), and cTFH-CM (CD45RA-CCR7+), and lower SMNE+ T cell proliferative capacity than the other two groups, whereas I-I-A showed a higher proportion and number of virus-specific CD4+ T cells than I-I-R, as determined in ex vivo experiments. Our data confirmed different SARS-CoV-2-specific antibody profiles among the three different vaccination strategies and also provided insights regarding BCR usage and T/B cell activation and differentiation, which will guide a better selection of vaccination strategies in the future.IMPORTANCEUsing the same laboratory test to avoid unnecessary interference due to cohort ethnicity, and experimental and statistical errors, we have compared the T/B cell immune response in the same cohort sequential vaccinated by different types of COVID-19 vaccine. We found that different sequential vaccinations can induce different dominant BCR usage with no significant neutralizing titers and RBD+ B-cell phenotype. Recombinant protein vaccine can induce higher numbers of regulatory T cells, circulating TFH (CTFH)1, CTFH17, and CTFH-CM, and lower SMNE+ T-cell proliferative capacity than the other two groups, whereas I-I-A showed higher proportion and number of virus-specific CD4+ T cells than I-I-R. Overall, our study provides a deep insight about the source of differences in immune protection of different types of COVID-19 vaccines, which further improves our understanding of the mechanisms underlying the immune response to SARS-CoV-2.